Testing the parameters of hot-mix asphalt incorporating asphalt granulate - Paula Jędrzejczyk; Zbigniew Respondek (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2024)
In recent years, the scale of use of recycled asphalt pavements for the production of hot mix asphalt (HMA) in Poland has been much smaller than in most other developed countries. Recently issued legal regulations and technical guidelines give hope for significant progress in this field. The article aims to investigate the parameters of HMA containing asphalt granulate (AG) in the context of using locally available materials and increasing the percentage of AG above the maximum amount recommended by current guidelines. It was found that the content of up to 40% AG used as an aggregate replacement does not significantly worsen the key parameters of HMA intended for the construction of an asphalt concrete subbase. The use of asphalt granulate may also result in a significant (up to approximately 50%) reduction in the consumption of road bitumen for the production of HMA.